Optimalisasi Identitas dan Keuangan UMKM melalui Edukasi Branding dan Pencatatan Keuangan Sederhana: Pengabdian - Nurbaeti Rizkiyah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Badak Village is a rural area rich in natural resources, particularly in agriculture, livestock, and local crafts. One of its key strengths lies in the presence of Micro, Small, and Medium Enterprises (MSMEs) managed by local residents, focusing on products such as agricultural goods, traditional snacks, and handmade crafts. MSMEs play a significant role in both national and local economic development, yet many still face major challenges in branding and financial management. Weak branding makes it difficult for products to be recognized by consumers, while poor financial recording hinders decision-making and access to financing. To address this, university students participating in a community service program (KKN) conducted educational and participatory training sessions. The training was divided into two main topics: strengthening business identity through basic branding and simplifying financial management. Through this program, MSME owners learned the importance of having a meaningful business name, effective logo design, attractive packaging, and consistent financial records. As a result, participants began to realize the value of balancing branding with sound financial practices to support sustainable business growth. This initiative marked the beginning of positive change for MSMEs in Badak Village.